Intestinal Microbiota-Derived GABA Mediates Interleukin-17 Expression during Enterotoxigenic Escherichia coli Infection - Ren, Wenkai; Yin, Jie; Xiao, Hao; Chen, Shuai; Liu, Gang; Tan, Bie; Li, Nengzhang; Peng, Yuanyi; Li, Tiejun; Zeng, Benhua; Li, Wenxia; Wei, Hong; et al. (Frontiers in Immunology, 2017)
Intestinal microbiota has critical importance in pathogenesis of intestinal infection; however, the role of intestinal microbiota in intestinal immunity during enterotoxigenic Escherichia coli (ETEC) infection is poorly understood. The present study tested the hypothesis that the intestinal microbiota is associated with intestinal interleukin-17 (IL-17) expression in response to ETEC infection. Here, we found ETEC infection induced expression of intestinal IL-17 and dysbiosis of intestinal microbiota, increasing abundance of γ-aminobutyric acid (GABA)-producing Lactococcus lactis subsp. lactis. Antibiotics treatment in mice lowered the expression of intestinal IL-17 during ETEC infection, while GABA or L. lactis subsp. lactis administration restored the expression of intestinal IL-17. L. lactis subsp. lactis administration also promoted expression of intestinal IL-17 in germ-free mice during ETEC infection. GABA enhanced intestinal IL-17 expression in the context of ETEC infection through activating mechanistic target of rapamycin complex 1 (mTORC1)-ribosomal protein S6 kinase 1 (S6K1) signaling. GABA-mTORC1 signaling also affected intestinal IL-17 expression in response to Citrobacter rodentium infection and in drug-induced model of intestinal inflammation. These findings highlight the importance of intestinal GABA signaling in intestinal IL-17 expression during intestinal infection, and indicate the potential of intestinal microbiota-GABA signaling in IL-17-associated intestinal diseases.